2018
DOI: 10.1111/luts.12252
|View full text |Cite
|
Sign up to set email alerts
|

Higher urge severity score predicts resumption of overactive bladder (OAB) medication following discontinuation of mirabegron treatment in patients with OAB

Abstract: Objectives: This study investigated factors predicting the resumption of mirabegron following its discontinuation with successful treatment of overactive bladder (OAB).Methods: In all, 374 OAB patients reporting an improvement in subjective symptoms after a minimum of 3 months treatment with mirabegron 25 mg, q.d., were screened. Those wanting to continue with the medication (n = 109) were excluded from the study. The remaining 265 patients discontinued mirabegron and their outcomes were evaluated at baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that patients who were successfully treated with mirabegron for ≥ 3 months, nearly half requested the resumption of mirabegron after discontinuation. There is no wonder why 47.6% of patients in group 4 preferred to resume M25 after treatment with M25 + S5 in this study [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that patients who were successfully treated with mirabegron for ≥ 3 months, nearly half requested the resumption of mirabegron after discontinuation. There is no wonder why 47.6% of patients in group 4 preferred to resume M25 after treatment with M25 + S5 in this study [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one recent clinical trial, mirabegron treatment was discontinued in OAB patients with symptom improvement after 3-month medication [ 39 ]. Among 682 patients treated with mirabegron for 3 months, 321 (47.1%) did not come back, 109 (16.0%) continue mirabegron treatment due to symptom persist, and 252 (36.9%) discontinued medication and return for follow-up visit.…”
Section: H Ow Long Should We Give Overactive Bladder Medicamentioning
confidence: 99%
“…Kim et al 2 and Lee et al 3 reported 52%–62% OAB recurrence rates in the patients who discontinued antimuscarinics after successful results. Wang et al 4 reported that 109 (16%) patients continued mirabegron treatment, and 252 (36.9%) patients, who discontinued the treatment, came back for re‐treatment among a total of 682 patients, indicating that 53% of patients in total have not stopped the drug management. However, this study reported the results during an observation period of 3 months; therefore, they could find more relapsed cases if they followed up for a longer term.…”
Section: Introductionmentioning
confidence: 99%